Reasons for the loss of animal genetic resources (AnGR) and the importance of IK in AnGR management - Alemayehu, N.; Gebru, G.; Drucker, Adam G. (Ethiopian Society of Animal Production, 2004)
Reasons for the accelerating loss of animal genetic resource (AnGR) diversity include indiscriminate crossbreeding, breed substitution, natural disasters and civil strife. The mechanisms through which these factors impact AnGR diversity are identified together with indigenous AnGR management practices that could be integrated into a scientifically based conservation strategy.